Szempontok az Alföld legkésőbbi avar horizontjába sorolható lelőhelyek kritikai vizsgálatához - Mészáros Boglárka (Monográfiák a Szegedi Tudományegyetem Régészeti Tanszékéről, 2017)
One of the favourite and also of most difficult problems in the archaeology of the Carpathian Basin – profoundly dealt with by the scholarship – is the survival of the Avars in the period of Hungarian Conquest. Archaeologists examine objects classified as the latest Avarian horizon not in itself, but in the context of complete group of problems of the 9th century. Unfortunately, this approach presents a risk of pre-concepts. In addition, we frequently face uncertainties, because there are many inaccuracies in the relative and absolute chronology of the latest Avarian find horizon. In my opinion, we should give separate answers to the basic questions of the problem, that is to say, one should focus on the precise composition of the find material and its internal relationship. After fulfilling these tasks, we’ll be able to answer the question of the Avarian survival. In order to completely outline the latest find horizon, I start my research with the critical examination of the find material coming from the latest Avarian cemeteries of the Great Hungarian Plain. In the present study, I deal only with the sites included into the ADAM (Archäologische Denkmäler der Awarenzeit in Mitteleuropa) as ones belonging to the 9th century, the dating of which is not relevant any more.